1998
DOI: 10.1055/s-2007-995821
|View full text |Cite
|
Sign up to set email alerts
|

Derangements of Coagulation and Fibrinolysis in Critically III Patients with Sepsis and Septic Shock

Abstract: In patients with sepsis and septic shock, both coagulation and fibrinolysis are activated frequently leading to the syndrome of diffuse intravascular coagulation (DIC). The different mechanisms leading to abnormalities in coagulation and fibrinolysis are discussed in detail. The coagulation and fibrinolytic system appear to be influenced by the septic process largely independently, leading to a procoagulant imbalance between these systems. Coagulation is initiated by mediator-induced expression of tissue facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(169 citation statements)
references
References 106 publications
6
144
0
8
Order By: Relevance
“…2, A-D). TAT complexes formed after neutralization of thrombin by antithrombin III have been used as a surrogate marker for thrombin generation (39). In the present study, we observed that CLP markedly increased plasma levels of TAT complexes and that the administration of clodronate significantly reduced CLP-induced TAT complex levels in plasma by 54% (Fig.…”
Section: Resultssupporting
confidence: 63%
“…2, A-D). TAT complexes formed after neutralization of thrombin by antithrombin III have been used as a surrogate marker for thrombin generation (39). In the present study, we observed that CLP markedly increased plasma levels of TAT complexes and that the administration of clodronate significantly reduced CLP-induced TAT complex levels in plasma by 54% (Fig.…”
Section: Resultssupporting
confidence: 63%
“…High levels of PAI-1 inhibit the fibrinolytic system by preventing the formation of plasmin from plasminogen and promote thrombosis (6,7). An elevated concentration of PAI-1 correlates with an increased rate of ischemic arterial disease (8) as follows: atherosclerosis, angina pectoris (9 -14), and myocardial infarction (15)(16)(17)(18)(19)(20)(21)(22), as well as with deep vein thrombosis and disseminated intravascular coagulation (23)(24)(25). Because complete inactivation of PAI-1 is not lifethreatening (26 -28), the development of new approaches to the therapeutic neutralization of PAI-1 is a subject of many studies (for review see Refs.…”
mentioning
confidence: 99%
“…Sepsis patojenezinde enflamasyon gelişimi, kompleman sistem etkinleşmesi ve koagülasyon gelişmesi ve fibrinolizde bozukluklar yer almakta olup, sitokinler, proteazlar, lipit mediyatörler, gaz yapısındaki maddeler ve vazoaktif peptitler önemli rol oynamaktadır (Şekil 4) (20)(21)(22)(23)(24). Toksinler dolaşıma karıştığı zaman makrofajları etkinleştirerek MAPK ve NF-κB aracılıklı interlökin (IL)-1, IL-6, IL-8 ve tümor nekrozlaştırıcı faktör-α (TNF-α) gibi birçok enflamatuvar sitokin salıverilmesine yol açmaktadır.…”
Section: Toll-interleukin 1 Receptor Domain-containing Adapter-induciunclassified